Ruminal degradation and in vivo digestibility of processed rapeseed meal - Syrjälä-Qvist, Liisa; Pekkarinen, Eeva; Setälä, Jouko (Agricultural and Food Science, 1984)
The digestibility and nutritive value of rapeseed meal processed in different ways were studied with adult rams fed on alkali-treated straw. The rumen degradability was determined by the nylon bag technique. The rapeseed meal feeds were: 1) untreated rapeseed meal, 2) heat-treated rapeseed meal (2—5 sec. at over 100°C), 3) heat-treated rapeseed meal + 5 % urea phosphate and 4) heat-treated rapeseed meal + 10 % rapeseed hulls. The heat treatment reduced the rumen degradation and in vivo digestibility of the rapeseed meal, although not significantly (P > 0.05). Addition of urea phosphate to the heat-treated rapeseed meal increased the ruminal degradability of the crude protein and improved the digestibility of all the constituents of the rapeseed meal, especially that of crude fibre (P > 0.05). The rapeseed hulls had no noticeable effect on digestibility.